Diagnostic accuracy of combinations of serological biomarkers for identifying clinical tuberculosis - Zaida Araujo; Noe Macias-Segura; Juan Ernesto Lopez-Ramos; Jacobus Henry de Waard; Magnolia Vanegas; Manuel Alfonso Patarroyo; Antonio Salgado; Jose Antonio Enciso-Moreno (Journal of Infection in Developing Countries)
Introduction: Confirmation of tuberculosis (TB) cases in endemic TB settings is a challenge; obtaining fast and cheap, though accurate, diagnostic tools such as biomarkers is thus urgently needed to enable the early detection of TB. This paper evaluates the diagnostic accuracy of combinations of host serological biomarkers for identifying TB.